2016
DOI: 10.1002/cctc.201501423
|View full text |Cite
|
Sign up to set email alerts
|

Branched Selectivity in the Pd‐Catalysed Methoxycarbonylation of 1‐Alkenes

Abstract: The methoxycarbonylation of alkenes by palladium(II) complexes with P,O‐donor ligands [(2‐methoxyphenyl)diphenylphosphine (L‐2), bis(2‐methoxyphenyl) phenyl phosphine (L‐3) and tris(2‐methoxyphenyl) phosphine (L‐4)] has been investigated. The results show that the Pd complexes derived from these ligands provide high regioselectivity for the branched esters from 1‐pentene and 1‐hexene (>80 %). Various parameters (including temperature, pressure, acid concentration) were optimized to improve the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…With respect to steric bulk, the relatively sterically demanding PCy 3 afforded lower conversions of 37%, compared to the less bulkier PPh 3 , which gave conversions of 91%. This trend may be assigned to a hindered substrate coordination to the palladium metal when the bulky PCy 3 phosphine is used . In addition, we noted that the more electron rich P (OMe) 3 group resulted in lower percentage conversion (56%) compared to PPh 3 (91%).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…With respect to steric bulk, the relatively sterically demanding PCy 3 afforded lower conversions of 37%, compared to the less bulkier PPh 3 , which gave conversions of 91%. This trend may be assigned to a hindered substrate coordination to the palladium metal when the bulky PCy 3 phosphine is used . In addition, we noted that the more electron rich P (OMe) 3 group resulted in lower percentage conversion (56%) compared to PPh 3 (91%).…”
Section: Resultsmentioning
confidence: 79%
“…It has been widely reported that the use of different phosphine derivatives to stabilize the active palladium species significantly affect the catalytic performance of palladium complexes in methoxycarbonylation reactions . Complex 2 , was thus used to probe this feature using both chelating and monodentate phosphine groups, offering various electronic and steric properties (Table , entries 1, 7–9).…”
Section: Resultsmentioning
confidence: 99%
“…Such an observation has been made before and associated with enhanced isomerization reactions at higher temperatures. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…Such an observation has been made before and associated with enhanced isomerization reactions at higher temperatures. [47] The dependence of catalytic performance of complex Pd5 on CO pressure was scrutinized through varying it from 50 to 70 bar (Table 3, entries 5, 7, and 8). Expectedly, a higher pressure of 60 bar concomitantly led to enhanced yields of 94%, in comparison with percentage yields of 66%, observed at 50 bar.…”
Section: Investigation Of the Impacts Of Reaction Conditions On Metho...mentioning
confidence: 99%
See 1 more Smart Citation